EVALUASI PELAKSANAAN PROGRAM EXPANDING MATERNAL AND NEONATAL SURVIVAL (EMAS) UNTUK MENURUNKAN ANGKA KEMATIAN IBU DAN ANAK - Sri Melda Br Bangun; Basyariah Lubis (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Increasing the degree of maternal and child health continues to be carried out in Indonesia which is the achievement of the MDGs program. One program included in this program is Improving Maternal and Child Health. Based on the 2012 Indonesian Demographic and Health Survey (IDHS), the maternal mortality rate was 359 per 100,000 live births. This figure is still far from the target set in the MDGs, which is 102 per 100,000 live births in 2015. To achieve this target, the Maternal and Neonatal Survival (EMAS) program was created which focused on reducing maternal and child mortality. This study was conducted qualitatively with a case study design to evaluate the implementation of the EMAS program. Research locations in Batang Kuis Health Center and Sembiring Delitua Hospital. The informants of this study were the heads of the puskesmas, coordinating midwives, hospital management and the community. In-depth interviews were carried out using guidelines, by analyzing the results transcripts and describing them in the form of a matrix.From the results of the study it was found that the EMAS program in the first year had not reached the target because the application of the Information and Communication System of the Emergency Referral Network, the Public Health Gate Information System and the Strengthening and Learning Information System had not been implemented only in the system development stage. This is due to the lack of human resources in terms of technology and limited internet networks due to the different geographical conditions of each puskesmas. Suggestions to the health office and Puskesmas provide facilities and infrastructure in the implementation of the information system because this system focuses on addressing maternal and child emergencies by using the internet and SMS gateway as well as improving the ability of health workers to apply